La Indebida Utilización de la Boleta de Auxilio Disminuye la Efectividad en la Prevención de la Violencia - Cuesta Rosillo, Marlis Alexia (2022)
The present research thesis about “The Improper Use of the Aid Ticket Decreases the Effectiveness in the Prevention of Violence”, proposes to expose the incorrect use of the person who has the aid ticket as a victim through this protection measure, he/she misuses or acts in bad faith against who is known as the aggressor, resulting in negative aspects of said protection measure. Therefore, solutions to this social problem are also proposed. The present topic is an investigation, in which the penal sectors were covered, in addition to those that intervene in this type of legalities such as Constitutional Rights and the guarantees of laws such as the Law Against Violence against Women and the Family, Law to Prevent and Eradicate Violence Against Women and Code for Children and Adolescents. There are particular facts about this research work, such as the use of the aid ticket given by its bearer, the causes of this improper use, the solutions that are intended to be applied, and the reform proposal that is proposed as a control to this problem. Emphasizing that domestic violence is a social problem that will still persist but that it is sought to reduce these rates since "It is in the family where the most intense feelings are born and mature and where basic social learning is carried out." (Sanchez, 2001)